SINERGITAS SENABUNG DAN MITRA PADA KEGIATAN SOSIAL DI DESA CIWARNA KECAMATAN MANCAK KABUPATEN SERANG - April Laksana; Ade Idzhar; Intan Indria Dewi; Riska Ferdiana; Kenedi Kenedi; Agus Sunardi (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Community service conducted with the synergy between SENABUNG in social activities with the students of Kuliah Kerja Mahasiswa (KKM) from Universitas Bina Bangsa in community service in Ciwarna Village, Mancak Subdistrict, Serang Regency. This activity aims to contribute to the community with the support of communities, institutions, and partners in the form of community service. The results and discussions show that the synergy between SENABUNG in social activities with KKM students from Universitas Bina Bangsa has significant positive impacts on the community of Ciwarna Village. The effective collaboration between these two partners in this community service allows the optimization of resources and expertise, making the community service programs more targeted and efficient. The in-depth identification of community needs and active participation of local residents in the planning and implementation of social activities also contribute to the success of the program. The community service programs implemented cover various aspects of community life, such as education, health, environment, and economy. The development of capacity and empowerment of the community in Ciwarna Village also becomes the main focus by conducting relevant training, mentoring, and providing assistance. In conclusion, the synergy between SENABUNG in social activities with KKM students from Universitas Bina Bangsa in Ciwarna Village plays a crucial role in improving the quality of life of the local community. This collaboration reflects the spirit of cooperation and commitment of the university and students to actively contribute to solving social issues and enhancing community well-being